(1.2x+3.8)/4=(5.2x+1.8)/6

Simple and best practice solution for (1.2x+3.8)/4=(5.2x+1.8)/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1.2x+3.8)/4=(5.2x+1.8)/6 equation:



(1.2x+3.8)/4=(5.2x+1.8)/6
We move all terms to the left:
(1.2x+3.8)/4-((5.2x+1.8)/6)=0
We calculate fractions
(1.2x)/()+(-((5.2x+1.8)*4)/()=0
We calculate terms in parentheses: +(-((5.2x+1.8)*4)/(), so:
-((5.2x+1.8)*4)/(
We multiply all the terms by the denominator
-((5.2x+1.8)*4)
We calculate terms in parentheses: -((5.2x+1.8)*4), so:
(5.2x+1.8)*4
We multiply parentheses
20x+7.2
Back to the equation:
-(20x+7.2)
We get rid of parentheses
-20x-7.2
Back to the equation:
+(-20x-7.2)
We add all the numbers together, and all the variables
(+1.2x)/()+(-20x-7.2)=0
We get rid of parentheses
(+1.2x)/()-20x-7.2=0
We multiply all the terms by the denominator
(+1.2x)-20x*()-(7.2)*()=0
We add all the numbers together, and all the variables
(+1.2x)-20x*()=0
We get rid of parentheses
1.2x-20x*()=0

See similar equations:

| 40y-7=12y^2 | | -14=8-5x | | 5(3n-1)=55 | | 3(9+4x)=123 | | 2y-8=22-4y | | 2(7x-10)=36 | | 3x+2(x+7)=-11 | | 13×6=3x | | 38=4x+7x+5 | | (x-7/2)^2=0 | | -14-4x-3=3x-8-5x | | -x-3+7x=57 | | 6x+7=x+87 | | q(-4)+(1-q)(-4+5)=0 | | 1+8a=129 | | 1+8a=59 | | 3^4x+1=5 | | 8=10r+8-2r | | F=-6+2.5x | | X²-6x+20=0 | | 3(2x-4)=5x-(-3x+7) | | (x+9)2=121 | | 7y-2y-15=-5 | | X²+14x−176=0 | | X²+14x-176=0 | | 25x-5x=45+15 | | -x-59=85 | | 2a=-3a+1 | | x-39=74 | | -x+24=41 | | -9y=-2y-14 | | -9y=-2y-1 |

Equations solver categories